HGG-09. TARGETING FACILITATES CHROMATIN TRANSCRIPTION (FACT) AS A NOVEL STRATEGY THAT ENHANCES RESPONSE TO HISTONE DEACETYLASE (HDAC) INHIBITION IN DIPG. (1st June 2021) - Ehteda, Anahid; Simon, Sandy; Franshaw, Laura; Giorgi, Federico M; Liu, Jie; Hayden, Elisha; Rouaen, Jourdin; Pang, Chi Nam Ignatius; Pandher, Ruby; Mayoh, Chelsea; Tang, Yujie; Khan, Aaminah; et al.
Abstract: DIPG is an aggressive and incurable childhood brain tumour for which new treatments are needed. A high throughput drug screen of 3500 pharmaceutical compounds identified anti-malarials, including quinacrine as having potent activity against DIPG neurospheres. CBL0137, a compound modelled on quinacrine, is a novel anti-cancer compound which targets Facilitates Chromatin Transcription (FACT), a chromatin remodelling complex involved in transcription, replication, and DNA repair. CBL0137 effectively crosses the blood-brain barrier and has recently completed Phase I testing in adult patients. CBL0137 induced apoptosis in DIPG neurospheres and had profound cytotoxic activity against a panel of DIPG cultures. In a DIPG orthotopic model, treatment with CBL0137 significantly improved survival. We found that treatment with CBL0137 up-regulated TP53 and increased histone H3.3 acetylation and tri-methylation in DIPG cells. We therefore examined the interaction between CBL0137 and the histone deacetylase (HDAC) inhibitor panobinostat. In vitro experiments showed that the two agents had profound synergistic activity against DIPG neurospheres in clonogenic assays and enhanced caspase activation and apoptosis. The FACT subunit SSRP1 was found to directly interact with H3.3K27M and treatment with CBL0137 targeted this epigenetic defect, restoring histone H3.3 trimethylation and leading to tumor cell death. Transcriptomic analysis and immunoblotting indicated that combination treatment activated signalling pathways controlled by Retinoblastoma (RB)/E2F1 and subsequently increased phosphorylation and enzymatic activity of enhancer of zeste homolog 2 (EZH2). Consistent with the in vitro results, the combination of CBL0137 and panobinostat significantly prolonged survival in two independent orthotopic models of DIPG, while histological analysis showed restoration of H3K27me3 and decreased Ki67 positive cells. In addition to panobinostat, CBL0137 has been found to combine synergistically in vitro and in vivo with PARP and BET inhibitors. Given these promising results, a paediatric trial of CBL0137 will open through the Children's Oncology Group with an expansion cohort for DIPG patients.